Remote Access to Home Appliances: A Survey - Gawade, NB; Shinde, SB (International Journal of Computer Sciences and Engineering, 2025)
Now everything has evolved under Internet of Things. This domain embodied in a wide spectrum of networked products, systems, and sensors, which take advantage of advancements in computing power, electronics miniaturization, and network interconnections offering new ventures undiscovered previously. The IoT is the inter connection of physical devices (aka smart devices) equipped with electronics, software, sensor, actuators, and network connectivity enabling different components for data collection and exchange. The IoT allows objects to be sensed or controlled remotely across existing network infrastructure enabling direct embodiment of the physical world into digital world, leading to improved efficiency, accuracy and economic benefit apart from reduction in human intervention. The main objective of proposed system is to provide automation system with low cost & effective solution to electronic appliances.